Utilization of intrauterine contraceptive device in a District of West Bengal, India - Haldar, A; Baur, B; Bhattacharya, SK; Das, R; Mundle, M; Saha, TK (Journal of Institute of Medicine Nepal, 2012)
No abstract available Journal of Institute of Medicine, 2011: 33:1